A comparison of the foot and ankle condition between elite athletes and non-athletes - Kim, H.; Chung, E.; Lee, B.-H. (Journal of Physical Therapy Science, 2013)
[Purpose] The purpose of this study was to compare the foot and ankle condition between elite athletes and non-athletes. [Subjects] The elite athletes group included 85 subjects (28 males and 57 females) and the non-athletes group included 85 subjects (38 males and 47 females). [Methods] All subjects were evaluated for pain (visual analogue scale, VAS) and foot and ankle condition (The Foot and Ankle Disability Index, FADI, and The Foot and Ankle Outcome Score, FAOS). [Results] The elite athlete group showed significant differences from the non-athletes group in VAS, FADI (FADI, FADI-Sports), and FAOS (FAOS-symptoms, FAOS-pain, FAOS-ADL, FAOS-sports, FAOS-QoL). In addition, a meaningful difference in VAS, FADI-Sports, and FAOS-symptoms was observed between gymnasts and wrestlers. [Conclusion] The results of this study suggest the necessity prevention of injury to the foot and ankle of elite athletes, and for the development of exercise for the rehabilitation of foot and ankle injuries, because there is a difference in foot and ankle condition between elite athletes and non-athletes.